The evolution of microstructures and properties due to materials tool interaction during friction stir welding of similar and dissimilar al and Cu alloys - Dawood, Hasan Issa (School of Materials Engineering, 2015)
The primary objectives of this research are as follows to investigate the influence of small tool shoulder diameter and tool pin profiles on the material flow, microstructures and mechanical properties of the friction-welded butt joints of 6061 aluminum alloy; to study FSW parameters that would produce the best mechanical properties (i.e., rotational speeds and welding speeds with constant rubbing pressure) by butt joining two similar materials of 6061 aluminum alloy reinforced with 10 vol. % SiC powder from the welding volume; to investigate the influence of the surface roughness of the butt joints of 6061 aluminum alloy on weld quality achieved with the FSW technique; to study the effect of tool rotational speeds on the microstructures and mechanical properties of dissimilar materials of butt joint pure aluminum and copper with and without preheating on the copper side using a pinless welding tool.